Indeks Massa Tubuh terhadap Kadar Haemoglobin, Gula Darah dan Tekanan Darah Systole pada Remaja Putri - Ardhitya Sejati; Arlina Azka; Linda Yunitasari (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Obesity continues to increase among teenagers requiring special attention from the government and health workers. Obesity in adolescents is associated with an increased risk of diabetes mellitus and hypertension. On the other hand, underweight associated with the risk of anemia. This study aims to determine the correlation between body mass index and haemoglobin levels, blood sugar and systolic blood pressure in teenage girls. This research used cross-sectional study design. The research was conducted at Karya Rini Vocational School in May 2023. The research sample was all female students at Karya Rini Vocational School who were present at the time of the examination and were willing to be respondents. Data were analyzed using Rank Spearman Test. The results of the analysis show that the higher the body mass index, the higher the blood sugar level (r=0.291; p-value=0.023) and the higher the body mass index, the higher the systolic blood pressure in female adolescents (r=0.291; p-value=0.023). There is no relationship between body mass index and levels haemoglobin. However, there is a weak positive and significant relationship between body mass index and blood sugar levels and systolic blood pressure in teenage girls.